2011
DOI: 10.1590/s0074-02762011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum gametocyte carriage, sex ratios and asexual parasite rates in Nigerian children before and after a treatment protocol policy change instituting the use of artemisinin-based combination therapies

Abstract: The effects of artemisinin-based combination therapies (ACTs) on transmission of Plasmodium falciparum were evaluated after a policy change instituting the use of ACTs in an endemic area. P. falciparum gametocyte carriage, sex ratios and inbreeding rates were examined in 2,585 children at presentation with acute falciparum malaria during a 10-year period from 2001-2010. Asexual parasite rates were also evaluated from 2003-2010 in 10,615 children before and after the policy change. Gametocyte carriage declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…The above data are supported by other observations in children and adults, as detailed in Table 1[28,30,37,47,53,54,62,64,68,70]. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The above data are supported by other observations in children and adults, as detailed in Table 1[28,30,37,47,53,54,62,64,68,70]. …”
Section: Resultssupporting
confidence: 90%
“…Studies that report the effects of AL (in the absence of a comparator treatment) on gametocyte carriage/clearance are reviewed below and summarized in Table 1[28,30,37,47,53,54,62,64,68,70] (and Additional file 2[28,30,37,47,53,54,62,64,68,70]). Unless otherwise stated, all data discussed relate to patients with uncomplicated P. falciparum malaria.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that male gametocytes are generally more sensitive to antimalarial drugs than female gametocytes (28). This is highly significant as males may only represent ϳ20% of the total gametocyte population, and so assays without a sex-specific readout are not likely to identify male-targeted transmission-blocking compounds as they fall below the threshold of detection (31,32). As both gametocyte sexes are required for transmission, a combined male and female gametocyte readout is essential to maximize the screening potential of a gametocyte assay.…”
Section: Resultsmentioning
confidence: 99%
“…Although ACT shortens the duration of post-treatment circulation of mature gametocytes, a low density of mature sexual forms can persist after apparently complete clearance of trophozoites [14,35]. On day 28 after ACT treatment, a proportion of 12-40% of cured patients was found to be still gametocytaemic; a status which allows post-treatment malaria transmission [9,14,36,37]. Therefore, it can be assumed that the rebound of P .…”
Section: Discussionmentioning
confidence: 99%